Esensi HAM dalam Islam dan Relevansinya Dengan Demokrasi - Hatamar, Hatamar (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
Some Islamic political figures and commentators provide a comprehensive explanation of the essence of Islamic teachings (al-Qur'an) which emphasizes the recognition and protection of human rights (HAM). Islam has a genuine concept of human rights, which has been formulated even since the 7th century AD, namely since the emergence of Islam brought by the Prophet Muhammd, SAW which was later declared as human rights in Islam. All the contents of the Islamic version of the declaration are formulated based on the Qur'an and Sunnah. The actual effect of human rights in Islam, what humans have is not the rights they have brought from birth, as they arise in the notion of human rights in the Western world, but prescriptions that are given to humans, obtained or derived from sources interpreted as divine commands which includes rights and obligations. Therefore, what is called HAM is basically a human obligation to God, or God's rights to humans. In addition to owning a unique doctrine that is unique to Islamic human rights, of course it has values and essences that are similar to modern human rights which are now defeated, and even have values that are also present in the modern democratic system. universal values that support democracy, namely human rights, also have a central and essential place in Islamic teachings. Key Word: Essence, human rights in Islam and democracy.